Kendala Calon Pendidik Dalam Membuat Soal Pilihan Ganda Higher Order Thinking (Hot) - Joan Hesti Gita Purwasih (Institut Teknologi Sepuluh Nopember, 2020)
This study shows the causes of sociology education students' difficulties in making higher order thinking (HOT) tests. The method applied is the mix method through FGD data collection and questionnaires. The results showed that it was difficult for students to make HOT questions because 1) it was challenging to create stimulus questions, 2) lack of understanding of sociology material, 3) lack of mastery of Bloom's taxonomy application, 4) insufficient learning time, and 5) lecturer explanations were not good. Therefore, recommendations for effective learning improvement are needed, including using the principle of discovery learning